Retrospective analysis of computed tomographic colonography in a rural hospital. Issue 4 (20th January 2017) - Lee, Beom Jun; Balasingam, Adrian; Van den Bosch, Rene
Abstract: Introduction: The aims of this study were to investigate the diagnostic performance of computed tomography colonography (CTC) performed in a rural secondary hospital, and to describe the local pattern of CTC service provision. Method: A single site, retrospective observational analysis was conducted for all patients undergoing CTC during the 12‐month period from 1st of January to 31st of December 2014 with comparison to available colonoscopy. Results: There were 639 CTCs performed during the 12‐months period. The average time from referral to performance of CTC scan was 21.3 days. The diagnostic yield of CTC for CRC was 5.8%; and for large polyps ≥10 mm was 8.0%. The sensitivity and specificity of CTC for detecting CRC were 97.1% and 88.2% respectively. The most predictive symptoms for finding colorectal lesions were rectal bleeding and anaemia. The referral rate from CTC to colonoscopy was 16.9%. 63 patients (9.9%) had follow up recommendations made in their reports due to extracolonic findings. Conclusion: Computed tomography colonography performed in a rural secondary hospital provided sufficient sensitivity to detect large polyps or CRC. The specificity for CRC was lower than reported figures in the literature. Technical issue of CTC performance due to poor insufflation techniques was identified as a main contributing factor reducing CTC accuracy. CTCs were performed with acceptable waiting time and showed high overall diagnostic yield for colorectal neoplasm in a rural hospital.